Facebook as a tool to promote radiology education: expanding from a local community of medical students to all of South America - Zanon,Matheus (2018)
Abstract Objective: To assess the feasibility of Facebook to promote a radiology education project and to expand it from our university community of medical students to a wider audience. Materials and Methods: A group of 12 medical students created a Facebook page in June 2015, to contribute to radiology education in our university. From August 2015, clinical cases, including a brief explanation of clinical findings, along with different imaging modalities, were posted weekly and subscribers were encouraged to choose the most appropriate diagnosis. All cases were followed by the appropriate answer and an explanation to highlight imaging findings and diagnosis. Aiming to reach a larger audience, we also shared cases to a public Latin-American Facebook group, comprising a collective total of 28,182 physicians and medical students. Using the Facebook Insights tracking tool, we prospectively analyzed subscriber interaction with our page for 14 months. Results: During the period analyzed, 35 cases were posted. The most common imaging modalities were X-ray (n = 15) and computed tomography (n = 13). Before we began posting the weekly cases, our page had 286 likes. By October 2016, that number had grown to 4244, corresponding to an increase of 1484% and eight times the size of the medical student community at our institution (n = 530). Medical students made up most (76%) of the subscribers, followed by radiology residents (6%). An excellent or moderate contribution to personal image interpretation skills was reported by 65.3% and 33.1% of the users, respectively. Conclusion: Creating a Facebook page and posting weekly clinical cases proved to be an effective method of promoting radiology education.